The relationship between the fulfillment of spiritual needs and self-efficay in the elderly in nursing homes - Ni’mah, Nuris Sahilatun; Luthfa, Iskim; Aspihan, Mochammad (Universitas Islam Sultan Agung, 2023)
One of the factors that influence the self-care of the elderly is self-efficacy or self-confidence. Fulfillment of spiritual needs is an important factor for increasing the self-efficacy of the elderly in improving the quality of life. The purpose of this study was to analyze the relationship between fulfilling spiritual needs and the self-efficacy of the elderly in nursing homes. This research is a type of quantitative research and uses a cross-sectional study design with consecutive sampling techniques. The population in this study were 126 elderly in a nursing home. This research instrument uses a questionnaire. The data obtained was processed statistically using the Somers' d test. The results of this study showed that most of the elderly were aged 60-74 years with a percentage (68.3%), most of whom had the most sex, namely men, totaling 64 elderly with a percentage (50.8%), most of whom had the most religion, namely Muslim with a percentage of 96 elderly (76.2%), most of the education is elementary school with a total of 80 elderly with a percentage (63.5%), and most of the marital status are widowers with a total of 62 elderly with a percentage (49, 2%), most of the fulfillment of spiritual needs obtained a moderate majority score with a total of 108 elderly with a percentage (85.7%), and most of the self-efficacy obtained a moderate majority score with a total of 105 elderly with a percentage (83.3%). The results of somers'd research obtained a p value of 0.003 or a P value <0.05. This shows that there is a significant relationship between fulfilling spiritual needs and self-efficacy in the elderly in nursing homes.